(untitled) (Research, Society and Development, 2021)
Public concern over the routine use of antibiotics and ionophores in ruminant diets has increased due to the emergence of antibiotic-resistant bacteria that may represent risks to human health. Thus, efforts have been employed toward the development of alternative compounds to replace antibiotics and ionophores in ruminants’ diets. This study was carried out to investigate the in vitro effects of a blend containing cashew and castor vegetable oils and clove, eugenol, thymol, and vanillin essential oils on the activity of Gram-negative and Gram-positive ruminal bacteria. The experiments were designed so that each bacterium would be exposed to doses of 1.5,3.0, 4.5, and 6.0 mg/mL of the blend, with six replicates. Bacteria were cultivated on Hobson’s M2 medium in Hungate tubes. Antimicrobial activity was evaluated using a spectrophotometer at 600 nm. Readings were performed 0, 8, 12, and 24 hours after inoculation at 39º C. The four (1.5, 3.0, 4.5, and 6.0 mg/mL) concentrations of the blend of vegetable and essential oils inhibited the growth of Prevotella albensis, Prevotella bryantii, Prevotella ruminicola, and Anaerovibrio lipolyticus at 8 and 12 hours after the incubation. For Ruminococcus albus and Ruminococcus flavefaciens the addition of the blend of EO of concentrations of 3.0 and 4.5 mg/mL resulted in a greater impact on growth dynamics, with a reduction in optical density after 12 h of incubation. The findings of this research establish the combined action of the vegetable and essential oils was found to influence the growth of gram-negative and gram-positive bacteria and can be used as a rumen modulator. The study contributes to new information about the combined action of the vegetable and essential oils as antimicrobial agents on ruminant production.